Optimized Integration of Solar and Battery Systems in Water Distribution Networks - Anudeep Bhatraj; Elad Salomons; Mashor Housh (Engineering Proceedings)
Water Distribution Networks (WDNs) are traditionally known as significant energy users, leading to numerous studies aimed at enhancing their energy efficiency. However, despite the growing attention towards renewable energy, there has been limited focus on seamlessly incorporating sustainable energy solutions into WDNs. We present an optimization framework for designing and operating WDNs that integrate renewable energy sources. This model considers the unique constraints and needs of each system component. Drawing from realistic capital and operational cost estimates, this combined system refines the arrangement of both water and energy elements (for instance, determining the appropriate size for solar panels and battery systems and the capacity of pumping stations). It also suggests optimal daily operational strategies for the different seasons of the year, such as when to charge batteries or when to activate/deactivate pumps. Our findings highlight that when water and renewable energy systems are cohesively designed and operated, it can markedly boost the energy efficiency of WDNs, furthering the sustainability goals of both the water and energy sectors.